Overconfident Ceo And Firm Value: A Critical Review, Bibliometric Analysis, And Research Agenda - Ita Fionita; Edi Pranyoto (Prosiding International conference on Information Technology and Business (ICITB), 2022)
The results of the literature review from 138 articles succeeded in identifying variables, countries, perspectives, and research methodologies in the context of research on Overconfident CEO and Firm Value conducted during 2004 - 2021. The results of the study found that studies of Overconfident CEO and Firm Values were mostly conducted in developed countries. namely in the United State as the main object of research. Based on the research methodology, the study size of Overconfident CEO and Firm Value uses a quantitative approach. The experimental, survey and combinative research methods become more relevant to be used to provide a better picture of the Overconfident CEO and Firm Value. In addition, future research on Overconfident CEO and Firm Value can use several less frequent variables, namely CEO Narcissism, dividend policy, capital structure, investment, corruption, ownership structure, and acquisitions.Keywords— Overconfident CEO, Capital Structure, agency theory, behavioral finance, systematic review, bibliometric.